Efektivitas Pemberian Seduhan Bunga Rosella + Fe Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil di PMB Adhe Marhani Kelurahan Srimukti Tambun Utara - Abela Mayunita; Adhe Marhani (Universitas Malahayati Lampung, 2024)
ABSTRACT The prevalence of anemia in pregnant women is still high. In PMB Adhe Marhani, Srimukti Tambun Utara Village, and Bekasi Regency, the number of pregnant women who experience anemia each year has increased from 2020 to 2022, namely from 13.4% to 14.7%. The government is trying to meet the need for iron through a program of giving iron tablets for a minimum of 90 days. Rosella flowers have a high content of Fe and vitamin C, which can regulate iron absorption so that it can increase Hb levels in the body. To determine the effectiveness of giving rosella flower + Fe infusion to increase hemoglobin levels in pregnant women at PMB Adhe Marhani, Srimukti Tambun Utara Village, in 2023. Quasi-experimental design with pretest-posttest design with control group design. The sample is made up of pregnant women who experience anemia in January–February 2023. As many as 34 samples were taken using a purposive sampling technique. The intervention was 1 x 3 rosella petals in 200 cc of warm water for 7 days. Bivariate analysis used paired simple t test and independent t test. The results of the study showed that the mean difference in giving Fe tablets was 1.052 gr/dl and a p value of 0.000, and the mean difference in giving rosella flowers + Fe tablets was 1.906 gr/dl and a p value of 0.000. The results of the independent t-test obtained a p value = 0.000. There are differences in the effectiveness of giving rosella flower + Fe infusion to increase hemoglobin levels. Pregnant women are expected to diligently consume foods that contain iron and adhere to taking tablets together with rosella flower brew before going to bed so as to increase Hb levels in the mother's blood. Keywords: Provision of Rosella Flower Infusion, Fe Tablets, Hb Levels of Pregnant Women. ABSTRAK Prevalensi anemia pada ibu hamil masih tinggi. PMB Adhe Marhani Kelurahan Srimukti Tambun Utara Kabupaten Bekasi ibu hamil yang mengalami anemia setiap tahunnya mengalami peningkatan dari tahun 2020-2022 yaitu 13,4% menjadi 14,7%. Pemerintah berupaya memenuhi kebutuhan zat besi melalui program pemberian tablet tambah darah selama minimal 90 hari. Bunga rosella memiliki kandungan Fe dan vitamin C yang tinggi yang dapat mengatur penyerapan besi sehingga dapat meningkatkan kadar Hb dalam tubuh. Mengetahui efektivitas pemberian seduhan bunga rosella + Fe terhadap peningkatan kadar hemoglobin pada ibu hamil di PMB Adhe Marhani Kelurahan Srimukti Tambun Utara tahun 2023. Quasy eksperimental desain dengan rancangan pretest-posttest with control group design. Sampel adalah ibu hamil yang mengalami anemia pada bulan Januari-Februari tahun 2023 sebanyak 34 sampel dengan teknik purposive sampling. Intervensi diberikan 1 x 3 kelopak rosella dalan 200cc air hangat selama 7 hari. Analisis bivariat menggunakan uji paired simple t test dan t test independent. Hasil penelitian selisih mean pemberian tablet Fe 1,052gr/dl dan p value 0,000, selisih mean pemberian bunga rosella + tablet Fe 1,906gr/dl dan p value 0,000. Hasil uji t-test independent didapatkan nilai p value = 0,000. Terdapat perbedaan efektivitas pemberian seduhan bunga rosella + Fe terhadap peningkatan kadar hemoglobin. Ibu hamil diharapkan rajin mengkonsumsi makanan yang mengandung zat besi dan patuh dalam mengkonsumsi tablet bersamaan dengan seduhan bunga rosella sebelum tidur agar dapat meningkatkan kadar Hb dalam darah ibu. Kata Kunci: Pemberian Seduhan Bunga Rosella, Tablet Fe, Kadar Hb Ibu Hamil